(untitled) (World Bulletin of Education and Learning, 2025)
This article discusses the use of collaborative learning technologies in higher education, the impact of this method on improving the quality and efficiency of education; the ability of teachers, students, student groups, and the community to establish mutual cooperation, achieve consensus and unity, strive for a common goal, reveal the inner potential of each learner, and open up great opportunities for self-expression. It examines how the use of collaborative technologies in higher education can develop students’ social activity.